Transient Host Range Selection for Genetic Engineering of Modified Vaccinia Virus Ankara. (June 2000) - Staib, C.; Drexler, I.; Ohlmann, M.; Wintersperger, S.; Erfle, V.; Sutter, G.
Recombinant vaccinia viruses are extremely valuable tools for research in molecular biology and immunology. The extension of vaccinia vector technology to replication-deficient and safety-tested virus strains such as modified vaccinia virus Ankara (MVA) have made this versatile eukaryotic expression system even more attractive for basic and clinical research. Here, we report on easily obtaining recombinant MVA using stringent growth selection on rabbit kidney RK-13 cells. We describe the construction and use of new MVA vector plasmids that carry an expression cassette of the vaccinia virus host range gene, K1L, as a transient selectable marker. These plasmids allow either stable insertion of additional recombinant genes into the MVA genome or precisely targeted mutagenesis of MVA genomic sequences. Repetitive DNA sequences flanking the K1L gene were designed to remove the marker gene from the viral genome by homologous recombination under nonselective growth conditions. The convenience of this new selection technique is demonstrated by isolating MVA recombinants that produce green fluorescent protein and by generating MVA deletion mutants.